Crafts for Easter - Ross, Kathy (Katharine Reynolds), 1948-; Holm, Sharon Lane (Brookfield, Conn. : Millbrook Press, 1995)
Presents twenty simple craft projects for springtime and Easter that young children can make from everyday materials.
4 6 8 11 12 13 19 20 21 29 31 33 34
Keywords: Easter decorations -- Juvenile literature; Handicraft -- Juvenile literature; Easter decorations; Handicraft